The development and transformation of disfranchised teachers - Ishmail, Michelle Ingrid (University of the Free State, 1996)
This study deals principally with the development and transformation of teachers who were disfranchised in the Republic of South Africa. As the creation of a democratic, non-racial, united South Africa depends on the quality of the nation's education, the calibre of the teacher assumes a critical position. The purpose of this study is to establish whether the quality of education offered, provided for the development and transformation of these teachers. A historical overview of the major legislation which impacted on the lives of the disfranchised teacher is provided in order to give an understanding of the conditions which disfranchised teachers endured and how it affected their education in the segregated education departments. It emerges that education for the disfranchised was rigidly controlled by Central Government with the aim of preparing the disfranchised for perpetual subservience. Hence curricula for the various racial groups were diverse, it stressed obedience, communal loyalty and the rigid regimentation of teachers. Moreover none of these disfranchised teachers have completed their schooling untouched by the wave of protests, boycotts and demonstrations to oppose the entire political, economic, social and educational system which controlled their lives. In trying to accommodate prospective teachers who were unable to complete their schooling, curriculums in Colleges of Education were adapted and have thus become loaded with theory resulting in a skewed outcome at the expense of competency, efficiency, empowerment and the ability to bring about change in the classroom. The curriculums used after 1979 at Colleges of Education for the disfranchised, is outlined to ascertain if it indeed provided for the development and transformation of these teachers. In addition a brief synopsis of teacher education for the franchised is provided to determine the difference in provision. During the study, the key persons involved in teacher education (student teachers, teachers and lecturers) were asked to comment on anticipated shortcomings in their teacher education as well as difficulties they experienced due to these shortcomings. The research focused on 6 schools which operated under the ex-disfranchised departments as well as lecturers from a College of Education in Kimberley. The research shows that student teachers, teachers and lecturers agree that the practical aspect of teacher education needs more attention. On the basis of the research, certain changes in teacher education programmes for teachers, is recommended.
Dissertation (M.Ed. (Education))--University of the Free State (South Campus), 1996
Keywords: Teachers -- Social conditions; Teachers -- Training of -- South Africa